Finite p-Groups in Which Each Central Automorphism Fixes the Center Elementwise - Garg, Rohit (My University, 2011)
In this thesis we find necessary and difficult condition for a finite p-group of arbitrary nilpotency class such that each control automorphism fixes the centre element wise.
m.sc, MCAD
Keywords: Finite p-group; Central Automorphism